Co-governance for accountability : beyond 'exit' and 'voice' - Ackerman, John (2004)
Explores the theory and practice of society's participation in strengthening government accountability. Suggests that the best way to tap into the energy of society is through 'co-governance' which involves inviting social actors to participate in the core activities of the state.